Insights from a Genome-Wide Study of Pantoea agglomerans UADEC20: A Promising Strain for Phosphate Solubilization and Exopolysaccharides Production - Edith Elizondo-Reyna; Humberto Martínez-Montoya; Yahaira Tamayo-Ordoñez; María Antonia Cruz-Hernández; Mauricio Carrillo-Tripp; María Concepción Tamayo-Ordoñez; Gerardo de Jesús Sosa-Santillán; José Antonio Rodríguez-de la Garza; Mario Hernández-Guzmán; Virgilio Bocanegra-García; Erika Acosta-Cruz (Current Issues in Molecular Biology)
The genome sequence of Pantoea agglomerans UADEC20 is presented, which is a strain isolated from agricultural fields in northeast Mexico. The genome was assembled into 13 scaffolds, constituting a total chromosome size of 4.2 Mbp, with two of the scaffolds representing closed plasmids. The strain exhibits activity in phosphate solubilization and exopolysaccharide (EPS) production and secretion; therefore, we explored its biotechnological potential via its genome sequencing and annotation. Genomic analyses showed that a total of 57 and 58 coding sequences (CDSs) related to phosphate solubilization and EPS production were identified within its genome, in addition to a reduced number of CDSs related to drug resistance and phages. The comprehensive set of genes supporting phosphate solubilization, EPS synthesis, and secretion, along with its low virulence and antibiotic resistance levels, justify further research for its potential biotechnological application and possible use as a plant growth-promoting agent in the field. These findings suggest a unique genetic background in the P. agglomerans UADEC20 strain.